General Skills Strategies in Communication by Lecturers at the Beginning of Lectures to Students - Mukhtar Yusuf; Oktosiyanti MT. Abdullah (Journal for Lesson and Learning Studies, 2026)
The lack of implementation of lecturers' communication strategies at the beginning of the lecture has an impact on low student learning motivation. The urgency in interpersonal analysis, supportive classroom climate, and student learning preparation. The aim is to analyze the communication strategies used by lecturers and determine their influence on student learning motivation. The quantitative research approach with a descriptive correlational design. A sample of 160 respondents, consisting of lecturers and first semester students, was selected using a purposive sampling technique. Data were collected through questionnaires and observations, then analyzed using descriptive statistics, validity and reliability tests, Pearson correlation, and simple linear regression. The results showed that all instrument items were valid and reliable, with reliability values reaching 0.912 for communication strategies and 0.886 for learning motivation. Lecturers' communication strategies were in the high category (mean 4.12), as was student learning motivation (mean 4.08). There was a strong positive relationship between the two variables (r = 0.732). Regression analysis showed a significant influence of communication strategies on learning motivation with a coefficient of 0.699 and a contribution of 53.6%. It was found that lecturers' initial communication plays a critical role in building engagement and motivation to learn. In conclusion, strengthening lecturers' communication competencies is a strategic step to improve the quality of learning. The implication is that educational institutions need to incorporate communication training as part of their lecturers' professional development.